A Comparative Study on the General and Otolaryngological Manifestations of COVID-19 in the Hospitalized Population of the Telangana Region During the First and Second Waves - Pokala, Uma; Potnuru, Shilpa; Kanapalli, Sasikala; Sailesh, Agni Vishnu; P., Naveen (International Archives of Otorhinolaryngology, 2024)
Introduction Some common symptoms of coronavirus disease 2019 (COVID-19) are fever, cough, and shortness of breath. But ear, nose, and throat (ENT) manifestations such as loss of smell and taste are also very common.Objectives To compare the general and otorhinolaryngological manifestations of COVID-19 and to compare the treatments given and mortality rate during its two waves.Methods This retrospective study was conducted on severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) cases in a tertiary care teaching hospital. Six hundred patients were included in the 1st wave sample and 516 were in the 2nd wave sample. The data collected included demographics, comorbidities, general, and ENT symptoms, need for ventilatory support, oxygen therapy, and mortality for both the waves.Results Fever, malaise, and myalgia were more frequently presented in the first wave than in the second, whereas shortness of breath was more common in the second wave. In the second wave, a significant increase in anosmia cases was reported, whereas sore throat, nasal obstruction, dysphagia, nasal discharge, and sneezing were significantly reduced compared with the first wave (p < 0.001). The case fatality rate increased from 11.33 to 21.55% (p < 0.001) from the 1st to the 2nd wave. The patients who died in the second wave were younger than those in the first wave. Two doses of vaccination showed protection from the death over those not vaccinated and those who only received one dose (p < 0.05).Conclusion Ear, nose, and throat (ENT) manifestations are very common along with the general symptoms. As anosmia and dysgeusia are early presenting symptoms in COVID-19 patients, all physicians should screen patients for ENT symptoms.
Keywords: COVID-19; SARS-CoV-2; anosmia; dysgeusia